A 90 min Daytime Nap Opportunity Is Better Than 40 min for Cognitive and Physical Performance - Boukhris, Omar (Int J Environ Res Public Health, 2020)
This study examined the effects of different nap durations on attention and physical performance as well as mood states, sleepiness, perceived exertion (RPE), recovery (PRS), and muscle soreness (DOMS) in trained men. Fourteen amateur team sport players (age: 20.3 ± 3.0 years, height: 173.1 ± 6.7 cm, body-mass: 68.1 ± 6.6 kg) performed a maximal voluntary isometric contraction (MVIC) test, 5-m shuttle run, and the digit-cancellation (i.e., attention) test after a no-nap (N0) and 40-min (N40) and 90-min (N90) of nap opportunities. Subjective measurement of mood states, RPE, PRS and DOMS were determined. Compared to N0, both nap durations enhanced attention, MVIC, total distance (TD), and higher distance (HD) (p < 0.001), with a higher gain after N90 compared to N40 for attention (Δ = +3), MVIC (Δ = +30 N) and TD (Δ = +35 m) (p < 0.001). Total mood scores were better after N40 and N90 compared to N0 (p < 0.05), with lower scores after N90 compared to N40 (p < 0.05). DOMS and RPE scores were significantly lower and PRS was significantly higher after N40 and N90 compared to N0 and after N90 compared to N40 (p < 0.05). Although both nap opportunity durations were beneficial, N90 was better than N40 for improving physical performances and attention as well as the perception of recovery, reducing fatigue perception, muscle soreness, and negative mood states.